The Quality Of Brownies Substitution Of Moringa Flour - Anggraini, Indria Sari; Anggraini, Ezi; Gusnita, Wiwik; Kasmita, Kasmita (Universitas Negeri Padang, 2025)
Brownies are chocolate cakes that have a rather hard and dense texture, are blackish-brown in color and have a dominant chocolate flavor. Brownies are cakes made from wheat flour, sugar, cooking chocolate, cocoa powder, and oil. At this time, brownies are developing very rapidly so that many creations and flavors are found. For this reason, the author wants to vary it by substituting moringa leaf flour for the amount of wheat flour. The purpose of this study is to analyze the effect of moringa leaf flour substitution of 15%, 30% and 45% on the quality of brownies in terms of shape, aroma, texture and taste, this is motivated by the lack of much research so that it gives the author interest to research further. The type of research in this study is a pure experiment (true experiment). The research design used is a complete randomized design (CRD). Data was obtained from 3 limited panelists, using an organoleptic test format, each panelist responded to the sample by observing, smelling, touching, and tasting, then the data was analyzed by the variant analysis test (ANOVA). if it is different, it will be tested with the Duncan Multi Ranges Test (DMRT). Then data analysis is carried out, if the data obtained by Fcount is greater than Ftable, then it is continued with the Duncan test.